Return on Investment of a Work–Family Intervention: Evidence From the Work, Family, and Health Network. Issue 9 (September 2015) - Barbosa, Carolina; Bray, Jeremy W.; Dowd, William N.; Mills, Michael J.; Moen, Phyllis; Wipfli, Brad; Olson, Ryan; Kelly, Erin L.
Abstract : Objective: To estimate the return on investment (ROI) of a workplace initiative to reduce work–family conflict in a group-randomized 18-month field experiment in an information technology firm in the United States. Methods: Intervention resources were micro-costed; benefits included medical costs, productivity (presenteeism), and turnover. Regression models were used to estimate the ROI, and cluster-robust bootstrap was used to calculate its confidence interval. Results: For each participant, model-adjusted costs of the intervention were 690 and company savings were 1850 (2011 prices). The ROI was 1.68 (95% confidence interval, −8.85 to 9.47) and was robust in sensitivity analyses. Conclusion: The positive ROI indicates that employers' investment in an intervention to reduce work–family conflict can enhance their business. Although this was the first study to present a confidence interval for the ROI, results are comparable with the literature.